The Warcraft civilization : social science in a virtual world - Bainbridge, William Sims (MIT Press, 2010)
From the Publisher: World of Warcraft is more than a game. There is no ultimate goal, no winning hard, no princess to be rescued. WoW contains more than 5,000 possible quests, games within the game, and encompasses hundreds of separate parallel realms (computer serves, each of which can handle 4,000 players simultaneously). WoW is an immerse virtual world in which characters must cope in a dangerous environment, assume identities, struggle to understand and communicate, learn to use technology, and compete for dwindling resources. Beyond the fantasy and science fiction details, as many have noted, it's not entirely unlike today's world. In The Warcraft Civilization, sociologist William Sims Bainbridge goes further, arguing that WoW can be seen not only as an allegory of today but also as virtual prototype of tomorrow, of a real human future in which tribe-like groups will engage in combat over declining natural resources, build temporary alliances on the basis of mutual self-interest, and seek a set of values that transcend the need for war. Bainbridge explored the complex Warcraft universe firsthand, spending more than 2,300 hours there, deploying twenty-two characters of all ten races, all then classes, and numerous professions. Each chapter begins with one character's narrative, then goes on to explore a major social issue such as religion, learning, cooperation, economy, or identity through the lens of that character's experience. What makes WoW an especially good place to look for insights about Western civilization, Bainbridge says, is that it bridges past and future. It is founded on Western cultural tradition, yet aimed toward the virtual worlds we could create in times to come.